1991
DOI: 10.1073/pnas.88.20.8958
|View full text |Cite
|
Sign up to set email alerts
|

Functional map of the alpha subunit of Escherichia coli RNA polymerase: two modes of transcription activation by positive factors.

Abstract: The role of the a subunit of Escherichia coli RNA polymerase in transcription activation by positive factors was investigated using two reconstituted mutant RNA polymerases (containing C-terminally truncated a subunits) and three positive factors [the cAMP receptor protein (CRP), OmpR, and PhoB]. The mutant RNA polymerases did not respond to transcription activation by activator proteins that bind upstream of the respective promoters. Transcription by these mutant enzymes was, however, activated in the cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 33 publications
5
77
0
Order By: Relevance
“…The contact site on a for the CRP¹cAMP complex at the class I promoter lacP1 has been pinpointed to residues 265¹269 (N-terminal proximal portion of H1) (Zou et al 1992;Murakami et al 1996);and Sharif et al (1994) have shown that a mutation at A272 (H1) increases lacZ expression. That truncated a derivatives retaining these residues (a 271þ2 ¹a 316þ3 ) fail to respond to CRP¹cAMP (as has been shown previously for a 235 and a 256 in vitro Igarashi et al 1991b;Kolb et al 1993)) indicates sequences beyond the contact site play a role in activation, presumably by maintaining the correct spatial orientation and/or protecting the a C-terminal domain from proteolysis. An alternative possibility, that sequences beyond H1 interfere with activation by CRP¹cAMP unless correctly positioned, is unlikely given their rapid removal.…”
Section: In Vivo Transcriptional Activitysupporting
confidence: 59%
“…The contact site on a for the CRP¹cAMP complex at the class I promoter lacP1 has been pinpointed to residues 265¹269 (N-terminal proximal portion of H1) (Zou et al 1992;Murakami et al 1996);and Sharif et al (1994) have shown that a mutation at A272 (H1) increases lacZ expression. That truncated a derivatives retaining these residues (a 271þ2 ¹a 316þ3 ) fail to respond to CRP¹cAMP (as has been shown previously for a 235 and a 256 in vitro Igarashi et al 1991b;Kolb et al 1993)) indicates sequences beyond the contact site play a role in activation, presumably by maintaining the correct spatial orientation and/or protecting the a C-terminal domain from proteolysis. An alternative possibility, that sequences beyond H1 interfere with activation by CRP¹cAMP unless correctly positioned, is unlikely given their rapid removal.…”
Section: In Vivo Transcriptional Activitysupporting
confidence: 59%
“…The ␣ subunit, consisting of 329 amino acid residues, is composed of two structural domains, each responsible for distinct functions (1-3) and each forming independent structural domains connected by a protease-sensitive flexible linker (4-6). The amino (N)-terminal domain from residues 20 to 235 plays a key role in RNA polymerase assembly by providing the contact surface for ␣ dimerization and binding of ␤ and ␤Ј subunits (7-10), whereas the CTD from residues 235 to 329 plays a regulatory role by providing the contact surfaces for trans-acting protein factors and cis-acting DNA elements (11)(12)(13)(14).Whereas the regulation of many E. coli promoters involves a single factor, some promoters are regulated by two or more transcription factors, and such coregulation systems involving multiple species of transcription factors can couple gene expression to diverse environmental conditions. Knowledge of the molecular mechanism of prokaryotic transcription regulation involving more than two factors would contribute much to understanding of the events carried out in eukaryotes, because the regulation of gene transcription in eukaryotes generally involves the action of multiple transcription factors.…”
mentioning
confidence: 99%
“…The ␣ subunit, consisting of 329 amino acid residues, is composed of two structural domains, each responsible for distinct functions (1)(2)(3) and each forming independent structural domains connected by a protease-sensitive flexible linker (4)(5)(6). The amino (N)-terminal domain from residues 20 to 235 plays a key role in RNA polymerase assembly by providing the contact surface for ␣ dimerization and binding of ␤ and ␤Ј subunits (7)(8)(9)(10), whereas the CTD from residues 235 to 329 plays a regulatory role by providing the contact surfaces for trans-acting protein factors and cis-acting DNA elements (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In addition to the RNAPH s 4 domain, the interactions between the C-terminal domain of the a-subunit of RNAPH and OmpR or some other transcription activators were described [31][32][33][34][35] . To elucidate the initiation steps for transcription activation by PmrA, the interactions between PmrA-DNA and the s 4 or C-terminal domain of the a-subunit of RNAPH remain to be characterized, which is in progress.…”
Section: Discussionmentioning
confidence: 99%